Rosmarinus officinalis L. (rosemary) as therapeutic and prophylactic agent - De Oliveira, Jonatas Rafael [UNESP]; Camargo, Samira Esteves Afonso; De Oliveira, Luciane Dias [UNESP] (Springer Nature, 2019)
Rosmarinus officinalis L. (rosemary) is a medicinal plant native to the Mediterranean region and cultivated around the world. Besides the therapeutic purpose, it is commonly used as a condiment and food preservative. R. officinalis L. is constituted by bioactive molecules, the phytocompounds, responsible for implement several pharmacological activities, such as anti-inflammatory, antioxidant, antimicrobial, antiproliferative, antitumor and protective, inhibitory and attenuating activities. Thus, in vivo and in vitro studies were presented in this Review, approaching the therapeutic and prophylactic effects of R. officinalis L. on some physiological disorders caused by biochemical, chemical or biological agents. In this way, methodology, mechanisms, results, and conclusions were described. The main objective of this study was showing that plant products could be equivalent to the available medicines.
Keywords: Biological activities; Phytotherapy; Prophylactic effects; Rosemary; Rosmarinus officinalis L.; Therapeutic effects